“PAPA PUSING” SEBAGAI UPAYA MENINGKATKAN HASIL UJIAN NASIONAL DI SD NEGERI KARANGANYAR 1 - Chusniyati Nurfadhilah (WASIS : Jurnal Ilmiah Pendidikan, 2020)
The purpose of this paper is to describe the implementation of "Papa Pusing", the results and impact, constraints, and supporting "Papa Pusing" in SD Negeri Karanganyar 1.The method in this research is descriptive method. The population in this study were students of SD Negeri Karanganyar 1. The sample in this study were students of class VI SD Negeri Karanganyar 1 in the 2015/2016 academic year. The data analysis used was descriptive quantitative.The result of the implementation “Papa Pusing" is very effective in improving the creativity, knowledge, interest, and competence of students where from the initial conditions the average national exam of 65.2 to 72, the highest score of 26.4 UN initially increased to 28.75 and initially there are no students who scored 100 in the UN increased to two children who obtained a 100 in the UN. The effects are a lot of students who are enrolled in school favorite in the district of Kudus, students became increasingly religious, honest, disciplined and responsible, the confidence level of parents and the community increased due to the accountability of public schools also increased, the image of the school in the community the better and become an example and references other schools in the cluster-level national exam preparation. Obstacles encountered include too much pressure from parents to their children on reaching the maximum value, the absence of UN facilitation for students with special needs and excessive anxiety. Factors supporting namely the support and concern of all the school community and stakeholders to realize high quality graduates and good communication between teachers and parents